Pathways towards Objectivization of Art Expert Conclusions on the Evaluation of Pornographic Materials - Lyudmila K. Bondarenko (Теория и практика судебной экспертизы)
The paper examines the problem of evaluating the findings of artwork examination in terms of its scientific objectivity. Current negative trends in judicial proceedings in Russia are analyzed in connection with incorrect determination of the subject of forensic artwork analysis. Formal criteria distinguishing between different domains of social conscience are used to identify objective features that help to differentiate between pornographic materials and erotic artwork.